Determination of risk factors for child fall based on the Calgary - Isabella Lima Barbosa; DeborahPedrosa Moreira; Samira Valentim Gama Lira; Aline de Souza Pereira; Luiza Jane Eyre de Souza Vieira (Universidade de Fortaleza, 2010)
Objective: To determine risk factors for falls in children based on the Calgary Family Assessment Model (CFAM). Method: A qualitative approach, in which we interviewed six relatives of children who were admitted to an emergency hospital in Fortaleza, Ceara due to fall in the period from August to September, 2005. According to the CFAM we did the genogram and eco-map of two families (1) and (2). Results: By the genogram and eco-map of the families, we observed that (1) is a single parent family with six children, Roman Catholic, earns one minimum wage and attends both school and Family Health Basic Unit (UBSF). (2) is a nuclear family, with two children, Roman Catholic, earns three or more minimum wages and attends school, work and UBSF. Conclusion: The Calgary Family Assessment Model enabled to know the family structures of the children who had suffered falls and helped in defining the risk factors that exist within families and social environments in which these children attend. Family income, number of children, the presence or absence of fathers, schooling and lack of spaces for education support represent risk factors for these accidents.